2018
DOI: 10.1016/j.dib.2018.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Data on the effect of a muscimol treatment in caspase activation in descending neurons of lampreys after a complete spinal cord injury

Abstract: In this article, caspase activation in identifiable reticulospinal neurons of lampreys was inhibited after a complete spinal cord injury using a specific agonist of the GABAA receptor (muscimol). The data presented in this article are quantifications of fluorescent labelling of identifiable descending neurons of larval lampreys after a complete spinal cord injury using fluorochrome-labelled inhibitors of caspases (FLICA) and the corresponding statistical analysis. A single dose of muscimol decreased the intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…19 The beneficial effects of GABA appear to be mainly mediated through the activation of GABAB receptors in injured neurons; 19 although, recent work has also shown that the activation of GABAA receptors by muscimol inhibits caspase activation in identifiable neurons after SCI in lampreys. 20 Taken together, these data prompted us to study the possible effect of taurine in axon regeneration after SCI in lampreys. Here, we show that taurine levels increase 4 weeks after a complete SCI in the spinal cord of lampreys and that an acute taurine treatment promotes axon regeneration.…”
Section: Main Textmentioning
confidence: 99%
“…19 The beneficial effects of GABA appear to be mainly mediated through the activation of GABAB receptors in injured neurons; 19 although, recent work has also shown that the activation of GABAA receptors by muscimol inhibits caspase activation in identifiable neurons after SCI in lampreys. 20 Taken together, these data prompted us to study the possible effect of taurine in axon regeneration after SCI in lampreys. Here, we show that taurine levels increase 4 weeks after a complete SCI in the spinal cord of lampreys and that an acute taurine treatment promotes axon regeneration.…”
Section: Main Textmentioning
confidence: 99%
“…These giant neurons are very interesting as a model because they can be identified individually from brain to brain and because they show very different regenerative abilities after a complete SCI, which has led to the discovery of several molecules and signaling pathways regulating neuronal survival and axon regeneration (e.g. cAMP: [19] , [20] , [21] ; GABA: [22] , [23] , [24] ; Wnt: [25] ; Neogenin: [26] ; serotonin: [27] ; taurine: [13] ; gamma-secretase: [14] ; RhoA: [28] ; chondroitin sulfate proteoglycans [29] ). However, the presence of these giant reticulospinal neurons (e.g., the Mauthner cell) is characteristic of fish and amphibian species and similar giant descending neurons are not found in mammalian brains.…”
Section: Introductionmentioning
confidence: 99%